Determinations of optical positions for four extragalactic radio sources with CCD - Tang, Zh.; Wang, Sh.; Jin, W. (Кинематика и физика небесных тел, 1998)
From the twenty CCD observations made with the Schmidt telescope of Beijing Observatory, the optical positions of four radio sources 0851+202, 1228+126, 1442+101 and 1749+701 are given, using the method of single plate-constant and taking five catalogues as references: ACT, CMC, PPM, NPM and HIP. A comparison between our results and those of other authors is also made. За 20 ПЗЗ-спостереженнями, виконаними за допомогою телескопа Шмідта Пекінської обсерваторії, методом сталих окремої платівки визначені оптичні координати чотирьох радіоджерел 0851+202, 1228+126, 1442+101 та 1749+701. Як опорні використовувалися п'ять каталогів: ACT, CMC, PPM, NPM і HIP. Ми порівняли наші результати з даними інших авторів. По 20 ПЗС-наблюдениям, выполненным с помощью телескопа Шмидта Пекинской обсерватории, методом постоянных отдельной пластинки определены оптические координаты четырех радиоисточников 0851+202, 1228+126, 1442+101 и 1749+701. В качестве опорных использовались пять каталогов: ACT, CMC, PPM, NPM и HIP. Мы сравнили наши результаты с данными других авторов.